2009
DOI: 10.1007/s00277-009-0879-3
|View full text |Cite
|
Sign up to set email alerts
|

Absence of cardiac siderosis despite hepatic iron overload in Italian patients with thalassemia intermedia: an MRI T2* study

Abstract: Cardiac involvement in patients with thalassemia intermedia (TI) is characterized by a high-output state and pulmonary hypertension, with systolic left ventricle function usually being preserved. Myocardial iron overload in patients with TI has not been extensively studied. We conducted a cross-sectional study of 49 Italian patients with TI. Patient charts were reviewed and data collected for transfusion and iron chelation history, status of the spleen, and comorbid illnesses or infections. Blood samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 21 publications
4
43
0
1
Order By: Relevance
“…Hypercoagulability justifies the high rate of thromboembolic phenomena in patients with TI (Taher et al, 2006b(Taher et al, , 2008b and may explain other complications such as pulmonary hypertension (PHT) with secondary right heart failure (HF) (Aessopos et al, 2001;Taher et al, 2002). Ineffective erythopoiesis and chronic anaemia also lead to an increase in gastrointestinal iron absorption (Taher et al, 2009a), resulting in non-transfusional iron overload (similar to patients with hereditary haemochromatosis), in the liver and less so in the heart (Roghi et al, 2010;Taher et al, 2010e). Figure 1 highlights the proposed mechanism of iron overload in non-transfused patients with TI.…”
Section: Pathophysiology and Clinical Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypercoagulability justifies the high rate of thromboembolic phenomena in patients with TI (Taher et al, 2006b(Taher et al, , 2008b and may explain other complications such as pulmonary hypertension (PHT) with secondary right heart failure (HF) (Aessopos et al, 2001;Taher et al, 2002). Ineffective erythopoiesis and chronic anaemia also lead to an increase in gastrointestinal iron absorption (Taher et al, 2009a), resulting in non-transfusional iron overload (similar to patients with hereditary haemochromatosis), in the liver and less so in the heart (Roghi et al, 2010;Taher et al, 2010e). Figure 1 highlights the proposed mechanism of iron overload in non-transfused patients with TI.…”
Section: Pathophysiology and Clinical Complicationsmentioning
confidence: 99%
“…The initiation of chelation therapy in TI patients depends primarily on the extent of iron overload and rate of iron accumulation but, as with other aspects of the management of TI, clear Kirk et al, 2010). The available studies on MRI T2* assessment of cardiac iron in patients with TI failed to document cardiac siderosis despite significantly elevated LIC (Roghi et al, 2010;Taher et al, 2010e). Thus, in patients with TI, further research is still needed to better understand if (and when) detectable cardiac iron deposition can occur, and its correlation with cardiac morbidity and mortality.…”
Section: Iron Chelation Therapymentioning
confidence: 99%
“…40,44,47,51 Therefore, spot measurements of serum ferritin level may underestimate iron overload and delay therapy in patients with NTDT if they are to be interpreted in the same way as β-thalassemia major patients. Although current evidence suggests that patients with NTDT are less likely to develop cardiac siderosis, [50][51][52][53] cardiac magnetic resonance T2* assessment may still be warranted in older patients with high iron burden. 37 Data on the use of other iron overload indices, such as transferrin saturation or non-transferrin bound iron, in NTDT patients are still limited; therefore, no recommendations regarding their use in clinical practice can be made at this time.…”
Section: Iron Chelation Therapymentioning
confidence: 99%
“…49 Interestingly, cardiac siderosis and subsequent cardiac disease do not seem to be a major concern in NTDT, even in patients with considerably elevated liver iron concentration. [50][51][52][53] In a recent cross-sectional study of 168 patients with β-thalassemia intermedia, higher liver iron concentration values on magnetic resonance imaging were associated with a significantly increased risk of developing thrombosis, pulmonary hypertension, hypothyroidism, hypogonadism, and osteoporosis. 46 Levels of 5 mg Fe/g or over were associated with a considerable morbidity risk increase.…”
Section: Dysregulated Iron Homeostasis and Clinical Iron Overloadmentioning
confidence: 99%
“…A previous study stated that marked discordance was found between hepatic and cardiac iron overload as well as myocardial T2* and serum ferritin in a large study cohort comprising 106 patients with thalassemia major [19]. Similarly, studies conducted on thalassemia intermedia trait reported the absence of cardiac iron overload despite hepatic iron accumulation [16,20,21].…”
Section: Discussionmentioning
confidence: 99%